PENERAPAN KETENTUAN AMBANG BATAS BAKU MUTU LINGKUNGAN UDARA DALAM PEMBUKTIAN TINDAK PIDANA LINGKUNGAN AKIBAT KEBAKARAN HUTAN BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Sally Fisabillina; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
To determine the damage criteria and criteria for exceeding environmentalquality standards, an expert who indeed controls the field of environmental damage isrequired. Not only experts but conclusions for damage and exceeding quality standardsmust also be proven by accredited laboratory tests. The research entitled